PENINGKATAN KESEHATAN REMAJA MELALUI PENDIDIKAN KESEHATAN PENDEWASAAN USIA PERKAWINAN (PUP) DI SMA - Nurya Kumalasari; Rizki Sahara; Nurul kodiyah; Putri Apriliana; Ruli Mawarista (Jurnal Pengabdian kepada Masyarakat Cahaya Negeriku, 2024)
Background: Marriage age maturation (PUP) is an effort made by applying the age in the first marriage, which is as low as women marry at the age of 21 years and men at least 25 years, because at that age they hope to be able to solve problems and live a married life. Metodology : The activity was carried out by providing Reproductive Health Education on Marital Age Maturity (PUP) for high school students, then continued with a question and answer discussion. Results: The provision of education related to maturation of marriage age (PUP) is expected to increase knowledge of reproductive health and its application in the field can be supported by aspects that influence it and make productive generations able to prepare themselves for stunting prevention. Conclusion: Increasing students knowledge about Marital Age Maturity (PUP) so as to reduce the dropout rate in children.